Peranan World Wide Fund for Nature (WWF) dalam mengatasi perdagangan Harimau di Cina 2007-2012 - Mayangsari, Dwi; Tjarsono, Idjang (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2014)
This study investigated the role of WWF in dealing with the trade of tigers in China. This study also describes in tiger trade conditions in China. WWF as one of the world's leading independent conservation organizations, which are committed to environmental protection in the world. WWF has made a lot of changes to work with the community and government influence, in China. WWF has been monitoring the tiger trade. WWF also tries to connect and engage all stakeholders in addressing the tiger trade is happening in China . Training and education for the community and also the actors involved in involved in the trade and use of tiger . UNICEF has also been working with government agencies, other environments to help organizations cope with trafficking in tiger . Keywords : WWF, China ,illegal tiger trade